2022
DOI: 10.1136/bmjopen-2021-055214
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of a probiotic and a prebiotic examining metabolic and mental health outcomes in adults with pre-diabetes

Abstract: AimsTo evaluate the effect of the probioticLactobacillus rhamnosusHN001 and/or cereal enriched with oat-derived beta-glucan (OBG) on metabolic and mental health outcomes when administered to adults with pre-diabetes.Design2×2 factorial design randomised, parallel-groups placebo-controlled; double-blinded for probiotic, single-blinded for cereals.ParticipantsCommunity-dwelling adults aged 18–80 years with pre-diabetes: glycated haemoglobin (HbA1c) 41–49 mmol/mol.InterventionsCapsules containingLactobacillus rha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Consistent with these results, a recent study in pre-diabetes found that improvements in glycaemic outcomes in response to inulin supplementation could be predicted by better baseline glycaemic status (26). This has been supported in previous work, showing that supplementation with inulin improved outcomes in a pre-diabetes population with lower baseline HbA1c values (5.4 ± 0.1%, mean ± SD) ( 27) while another study using 4g oat beta-glucan found no effects on HbA1c or secondary outcomes in a pre-diabetes population with higher baseline values (HbA1c 6.4 ± 0.4%, mean ± SD) (28). These studies are consistent with our results, showing that patients who are earlier in the pre-diabetic disease pathway may be more likely to respond metabolically to prebiotic fibre interventions.…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with these results, a recent study in pre-diabetes found that improvements in glycaemic outcomes in response to inulin supplementation could be predicted by better baseline glycaemic status (26). This has been supported in previous work, showing that supplementation with inulin improved outcomes in a pre-diabetes population with lower baseline HbA1c values (5.4 ± 0.1%, mean ± SD) ( 27) while another study using 4g oat beta-glucan found no effects on HbA1c or secondary outcomes in a pre-diabetes population with higher baseline values (HbA1c 6.4 ± 0.4%, mean ± SD) (28). These studies are consistent with our results, showing that patients who are earlier in the pre-diabetic disease pathway may be more likely to respond metabolically to prebiotic fibre interventions.…”
Section: Discussionsupporting
confidence: 72%
“…The results of randomized controlled studies on pregnant women with gestational diabetes or obesity showed that probiotic intervention had no effect on glycemic control, but might improve lipid metabolism (18,19).In another study of prediabetes adolescents, it was not observed that oral probiotics could improve FBG and HbA1c after 4 months (20). Similarly, in a 24-week probiotic intervention study on adults with prediabetes, the goodness of glycosylated hemoglobin was not observed (21). Our studies are consistent with the conclusion of these studies that probiotics have a limited therapeutic effect on metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the two mentioned studies, in a 6-month study based on both probiotic and prebiotic administration in pre-diabetics, no signi cant difference found in SF-36 and depression, anxiety and stress scale (DASS-21) scores. However, there was no betterment in any of the metabolic or anthropometric outcomes, either (37). Positive impact of probiotic/synbiotic on the HRQoL was evident in healthy people (38) and in patients with IBS (39), systemic sclerosis (40), Cirrhosis (41) and minor digestive symptoms (42).…”
Section: Discussionmentioning
confidence: 99%